Yahoo Web Search

  1. Sort by

  1. Factor 4n^2 + 12n + 9 1). Look for a common factor--a number that can... in each parentheses the first term: 4n. Like this: (4n ) (4n ) [note that the exponent for the x in...

    2 Answers · Education & Reference · 29/10/2012

  2. For 4n^2-36 we first factor out the 4. 4n^2-36 =4(n^2-9) =4(n-3)(n+3) (it...

    3 Answers · Science & Mathematics · 03/11/2013

  3. 4n+6=-23 4n=-29 n=-29/4 4n+6=23 4n=17 n=17/4 The answers are...

    7 Answers · Science & Mathematics · 14/02/2007

  4. Notice that 4n^2 - 1 = (2n)^2 - 1^2 = (2n + 1)(2n - 1), so we have: 1/(4n^2 - 1) = 1/[(2n + 1)(2n.... Now, let us compute the following partial sum: ∑ 1/(4n^2 - 1) (from n=3 to N). We can compute this using the above partial...

    3 Answers · Science & Mathematics · 25/11/2012

  5. [ x^(4n+1) + x^(5n) ] / [ x^(6n) - x^(5n+2) ] = { x^(4n+1) [ 1 + x^(n-1) ] } / { x^(5n+2) [x^(n-2) - 1] } = [ 1 + x^(n-1...of last 3 expressions --- General comment 2n,4n,6n,etc powers yield perfect squares 3n,6n,9n,etc...

    2 Answers · Science & Mathematics · 20/08/2013

  6. 4N(N + 3) + 7N = 34 (distribute) 4N^2 + 12N + 7N = 34 (combine like terms) 4N^2 + 19N = 34 (subtract 34 from both sides) 4N^2 + 19N...

    1 Answers · Education & Reference · 30/08/2010

  7. 4n^2 + 23n - 6 (multiply 4 and -6, which is -24; find two integers that multiply... -1 and 24, and write them into the expression as n-terms) 4n^2 + 24n - n - 6 (group terms into pairs) (4n^2 + 24n) + (-n - 6) (factor...

    1 Answers · Education & Reference · 18/08/2009

  8. The 4n + 2n is a strategy for producing triploid (3n) organisms... triploids often grow faster than the diploid. The 4n (tetraploid or amphi-diploid) parent is often a 2n (diploid) that had ...

    1 Answers · Science & Mathematics · 05/12/2007

  9. 4n - 5 = 3n + 2, Add 5 to both sides. So to get rid of the - 5 on the left. 4n = 3n + 7 Subtract 3n from both sides. So to get...

    6 Answers · Education & Reference · 23/01/2012

  10. Is it 3 = √(4n) + 8 - n or 3 = √(4)n + 8 - n? If you meant 3 - 8 + n = √(4n) -5 + n = √(4n) (-5 + n)^2 = (√(4n))^2 (-5 + n)(-5 + n) = 4n 25 - 5n -5n +n^2 = 4n n^2 - 10n - 4n + 25 = 0 n^2 - 14n + 25 = 0 x =[ -b ± √(b²-4ac)] / 2a ...

    2 Answers · Science & Mathematics · 15/03/2014

  1. Try asking your question on Yahoo Answers